Identification of prognostic subtypes and the role of FXYD6 in ovarian cancer through multi-omics clustering - Ma, Boyi; Ren, Chenlu; Gong, Yun; Xi, Jia; Shi, Yuan; Zhao, Shuhua; Yin, Yadong; Yang, Hong (Frontiers in Immunology, 2025)
BackgroundOvarian cancer (OC), as a malignant tumor that seriously endangers the lives and health of women, is renowned for its complex tumor heterogeneity. Multi-omics analysis, as an effective method for distinguishing tumor heterogeneity, can more accurately differentiate the prognostic subtypes with differences among patients with OC. The aim of this study is to explore the prognostic subtypes of OC and analyze the molecular characteristics among the different subtypes.MethodsWe utilized 10 clustering algorithms to analyze the multi-omics data of OC patients from The Cancer Genome Atlas (TCGA). After that, we integrated them with ten different machine-learning methods in order to determine high-resolution molecular subgroups and generate machine-learning-driven characteristics that are both resilient and consensus-based. Following the application of multi-omics clustering, we were able to identify two cancer subtypes (CSs) that were associated with the prognosis. Among these, CS2 demonstrated the most positive predictive outcome. Subsequently, five genes that constitute the machine learning (ML)-driven features were screened out by ML algorithms, and these genes possess a powerful predictive ability for prognosis. Subsequently, the function of FXYD Domain-Containing Ion Transport Regulator 6 (FXYD6) in OC was analyzed through gene knockdown and overexpression, and the mechanism by which it affects the functions of OC was explored.ResultsThrough multi-omics analysis, we ascertained that the high-risk score group exhibits a poorer prognosis and lack of response to immunotherapy. Moreover, this group is more prone to display the “cold tumor” phenotype, with a lower likelihood of benefiting from immunotherapy. FXYD6, being a crucial differential molecule between subtypes, exerts a tumor-promoting effect when knocked down; conversely, its overexpression yields an opposite outcome. Additionally, we discovered that the overexpression of FXYD6 can induce ferroptosis in OC cells, implying that a low level of FXYD6 in OC cells can safeguard them from ferroptosis. Insightful and more precise molecular categorization of OC can be achieved with a thorough examination of multi-omics data. There are significant consequences for clinical practice stemming from the discovery of risk scores since they provide a useful tool for early prognosis prediction as well as the screening of candidates for immunotherapy.